c a − b = a b + c = b a − c
What is the possible positive value of a + b + c a , if the equation above is fulfilled?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
S a y K = c a − b = a b + c = b a − c W e u s e r a t i o p r o p e r t y k = n m = q p , t h e n k = n + q m + p A d d i n g F i r s t t w o K = c + a a + c = 1 . A d d i n g a l l t h r e e K = a + b + c 2 a ∴ a + b + c a = 2 K = 0 . 5 .
I started this problem by giving values to two out of the three variables. Leaving the last as "x"
Example: Let a=2 b=1 and c=x
Which would give you: x 2 − 1 = 2 1 + x = 2 − x
But we would only need one pair of expressions to solve for x namely: 2 1 + x = 2 − x .
Solving for x you would get x=1, which gives us a=2, b=1, and c=1.Which would be true for the conditions given.
Now, if you subtitute the three values into the expression given you would get: 2 + 1 + 1 2 = 2 1
or in other words: 0.5
A nice way of solution. I never thought in this direction before !! Any more comments from any one for explaining this method further ?
c=2a , b=-a
a/(a+b+c)=a/(a-a+2a)=1/2 or 0.5
Can you please explain why c=2a and b=-a ? Thanks.
Problem Loading...
Note Loading...
Set Loading...
I h a v e a s o l u t i o n w i t h u s i n g j u s t t h i s : c a − b = b a − c c a − b = b a − c ( a − b ) b = ( a − c ) c b 2 − c 2 = a b − a c ( b − c ) ( b + c ) = a ( b − c ) b + c = a A n d n o w : a + b + c a = 2 a a = 0 . 5